Opportunities and Challenges of Women Librarians Continue Study Master in Yogyakarta - Zuraida, Shinta Sisca; Suyono, Hanny Chairany; Aliwijaya, Araf (Universitas Airlangga, 2024)
Introduction. Education is important for developing the competence and career of librarians, including women librarians. Currently, opportunities for continuing education are increasingly widespread for all professions. However, female librarians still often experience obstacles in continuing their Master's education both due to family and other factors. This study aims to determine the opportunities and obstacles of female librarians in continuing their Master's program studies to improve their competencies and careers. Method. This is qualitative research with a descriptive approach. Data collection techniques through interviews, observation, and documentation studies. Informants are 8 female librarians who are currently pursuing a Master's education in Yogyakarta. The collected data will then be analyzed descriptively, including data reduction, presentation, and conclusions. Discussion. Women librarians have opportunities for career advancement, academic skill development, and librarian competence improvement. In addition, female librarians face several challenges, including financial ability, adaptation to scientific standards, and family management. Conclusion. Increasing abilities and expertise is the main factor for female librarians to continue their master's education. The challenges faced come from internal and external factors of their environment. Keywords : Education; Master; Librarians; Opportunities; Challenge ABSTRAK Peluang dan Tantangan Pustakawan Perempuan Lanjut Studi Magister di Yogyakarta Pendahuluan. Pendidikan merupakan hal yang penting bagi pengembangan kompetensi dan karir pustakawan, termasuk pustakawan perempuan. Saat ini kesempatan melanjutkan Pendidikan semakin luas untuk semua profesi. Namun demikian, pustakawan perempuan masih sering mengalami kendala dalam melanjutkan pendidikan Magister-nya baik karena faktor keluarga maupun faktor lainnya. Tujuan penelitian ini untuk mengetahui peluang dan hambatan pustakawan perempuan dalam melanjutkan studi program Magister dalam meningkatkan kompetensi dan karir mereka. Metode. Ini adalah penelitian kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data melalui wawancara, observasi, dan studi dokumentasi. Informan adalah 8 pustakawan perempuan yang sedang menempuh pendidikan Magister yang ada di Yogyakarta. Data yang dikumpulkan kemudian akan dianalisis secara deskriptif meliputi reduksi data, penyajian data dan kesimpulan. Pembahasan. Pustakawan perempuan memiliki kesempatan untuk peningkatan jenjang karir, pengembangan keahlian akademis, dan peningkatan kompetensi kepustakawanan. Selain itu, ada beberapa tantangan yang dihadapi pustakawan perempuan antara lain kemampuan finansial, adaptasi mengikuti standar keilmuan, dan manajemen keluarga. Kesimpulan. Peningkatan kemampuan dan keahlian menjadi faktor utama pustakawan perempuan melanjutkan pendidikan magister. Tantangan yang dihadapi berasal dari faktor internal dan eksternal dari lingkungan mereka. Kata kunci: Pendidikan; Magister; Pustakawan Perempuan; Peluang; Tantangan